Family Adoption Program: An NMC-mandated Initiative - Hemangini Kishore Shah; Amrit Kaur Virk; Amol Dongre; Shib Shekhar Datta; Subodh S. Gupta (Indian Journal of Community Medicine)
The National Medical Commission (NMC) of India has introduced the Family Adoption Program (FAP) as a key initiative within the Competency-Based Medical Education (CBME) framework. FAP is designed to reshape medical education by deeply embedding students within communities, providing a platform for experiential learning that enhances their understanding of healthcare challenges beyond the clinical setting. Under the program, medical students adopt families in rural or underserved areas and work with them over an extended period, addressing health needs and fostering a holistic, socially responsive approach to care. This engagement allows students to understand the multifaceted determinants of health—such as social, economic, cultural, and environmental factors—that influence well-being and disease. Through direct interaction with families, students develop a community-centred approach to healthcare delivery, fostering continuity of care and empowering communities in managing their own health. This paper explores how FAP integrates community engagement into medical education, driving both student learning and community health outcomes. It outlines the theoretical underpinnings and practical implementation strategies of FAP, offering a roadmap for medical colleges to successfully integrate this initiative into their curricula. The paper highlights best practices and innovative approaches from institutions, emphasizing the need for institutional ownership, interdisciplinary collaboration, and partnerships with local communities to ensure long-term success. Additionally, it provides insights for scaling FAP nationally, positioning it as a transformative step towards cultivating compassionate, community-oriented healthcare professionals. By fostering deeper connections between medical students and communities, FAP has the potential to improve health equity and transform health care across India.